2023
DOI: 10.1038/s41467-023-39869-5
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of DIA proteomics data using MSFragger-DIA and FragPipe computational platform

Abstract: Liquid chromatography (LC) coupled with data-independent acquisition (DIA) mass spectrometry (MS) has been increasingly used in quantitative proteomics studies. Here, we present a fast and sensitive approach for direct peptide identification from DIA data, MSFragger-DIA, which leverages the unmatched speed of the fragment ion indexing-based search engine MSFragger. Different from most existing methods, MSFragger-DIA conducts a database search of the DIA tandem mass (MS/MS) spectra prior to spectral feature det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 79 publications
0
31
0
Order By: Relevance
“…Consequently, we adjusted this DIA method for LC–MS analysis without using FAIMS and only injecting around 150 ng of sample material (adapted Kawashima method) using the same MS system (Exploris 480). For the first evaluation, we prepared three two-species spike-in samples, which are often used in proteomics, , consisting of HEK-293 and E. coli K12 in three different concentrations: Only HEK, E.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, we adjusted this DIA method for LC–MS analysis without using FAIMS and only injecting around 150 ng of sample material (adapted Kawashima method) using the same MS system (Exploris 480). For the first evaluation, we prepared three two-species spike-in samples, which are often used in proteomics, , consisting of HEK-293 and E. coli K12 in three different concentrations: Only HEK, E.…”
Section: Resultsmentioning
confidence: 99%
“…A large ensemble of DDA runs, especially when complex peptide mixtures are prefractionated (by, e.g., SDS-PAGE or HPLC), are more likely to achieve high coverage with low FDR than DIA. Nonetheless, there are many efforts to improve the processing of DIA (e.g., ref ) and we are starting to develop a mechanism to integrate DIA data into the PeptideAtlas build process. However, we did include stable isotope labeled (multiplexed) proteome data sets, including isobaric iTRAQ and TMT, , dimethyl labeling, as well as N-terminomics data sets using TAILS or COFRADIC .…”
Section: Resultsmentioning
confidence: 99%
“…In this study, several published DIA-MS acquisition schemes were compared against a well-established DDA-MS workflow to determine an optimal method that optimizes sample throughput and peptide detection. We show that a sample-specific spectral library resulted in the highest number of peptides detected compared to a library-free approach and a pan-human library . Our group has previously shown that analysis of extracellular vesicles (EV) isolated from EPS-urine further increases the number of prostate proteins in EPS-urine .…”
Section: Introductionmentioning
confidence: 91%
“…Data-independent acquisition (DIA)-MS is an emerging tool for characterizing proteomes for its ability to increase throughput and reproducibility, yet there is limited consensus on an ideal downstream data analysis approach for the highly convoluted data generated . To investigate the utility of DIA-MS workflows for clinical biofluid cohorts, we evaluated various commonly used DIA-MS data analysis approaches using a large clinically heterogeneous cohort of urines from 199 patients with prostate cancer. These patients spanned the risk spectrum, from clinical ISUP grade Group 1 disease (associated with better prognosis) to clinical ISUP grade Group 5 disease (associated with worse prognosis) .…”
Section: Introductionmentioning
confidence: 99%